Nickel-catalysed enantioselective reaction of secondary phosphine oxides and activated vinylcyclopropanes - Huang, Zhuo; Liu, Xu-Teng; Cui, Ranran; Zhang, Qing-Wei (Organic & biomolecular chemistry, 2023)
Activated vinylcyclopropanes can form zwitterionic π-allylmetal species in the presence of transition metals and are widely used in organic synthesis. A nickel-catalyzed asymmetric allylation of secondary phosphine oxides with vinylcyclopropanes was described. Tertiary phosphine oxide products could be obtained with up to 91% yield and 92% ee. A nickel-catalyzed asymmetric allylation of racemic secondary phosphine oxides with racemic vinylcyclopropanes was described. The Tertiary phosphine oxide products were obtained with up to 91% yield and 92% ee.